Writing Africa in the short story - Emenyonu, Ernest 1939- (Boydell & Brewer, 2013)
African writers have, much more than the critics, recognized the beauty and potency of the short story. Always the least studied in African literature classrooms and the most critically overlooked genre in African literature today, the African short story is now given the attention it deserves. Contributors here take a close look at the African short story to re-define its own peculiar pedigree, chart its trajectory, critique its present state and examine its creative possibilities. They examine how the short story and the novel complement each other, or exist in contradistinction, within the context of culture and politics, history and public memory, legends, myths and folklore. Ernest Emenyonu is Professor of Africana Studies at the University of Michigan-Flint, USA; the editorial board is composed of scholars from US, UK and African universities. Nigeria: HEBN